Effect of the ammonium ion on proton conduction in porous ionic crystals based on Keggin‐type silicododecatungstate. Issue 11 (17th October 2018) - Miyazawa, Satoru; Hosono, Reina; Osuga, Ryota; Kondo, Junko Nomura; Uchida, Sayaka
Abstract : A porous ionic crystal based on Keggin‐type silicododecatungstate with ammonium ions shows high proton conductivity and low activation energy under high relative humidity, showing that protons migrate efficiently via rearrangement of the hydrogen‐bonding network formed by the NH4 + cations and the waters of crystallization. Abstract : Proton conduction in crystalline porous materials has received much attention from basic scientific research through to practical applications. Polyoxometalates (POMs) can efficiently transport protons because of their small superficial negative charge density. A simple method for enhancing proton conductivity is to introduce NH4 + into the crystal structure, because NH4 + can form hydrogen bonds and function as a proton carrier. According to these considerations, NH4 + was introduced into the porous structure of A 2 [Cr3 O(OOCH)6 (etpy)3 ]2 [α‐SiW12 O40 ]· n H2 O ( A = Li, Na, K and Cs; etpy = 4‐ethylpyridine) (I‐A + ) via topotactic cation exchange. The resulting compound, diammonium tris(4‐ethylpyridine)hexaformatooxidotrichromium α‐silicododecatungstate hexahydrate, (NH4 )2 [Cr3 (CHO2 )6 O(C7 H9 N)3 ]2 [α‐SiW12 O40 ]·6H2 O, showed high proton conductivity and low activation energy under high relative humidity (RH), suggesting that protons migrate efficiently via rearrangement of the hydrogen‐bonding network formed by the NH4 + cations and the waters of crystallization (Grotthuss mechanism). The proton conductivity and activation energy greatly decreased and increased, respectively, with the decrease in RH, suggesting that protons migrate as NH4 + and/or H3 O + under low RH (vehicle mechanism).